Fracturing fluid flow characteristics in shale gas matrix-fracture system based on NMR method - Wu, Jianfa; Yang, Xuefeng; Li, Jiajun; Liu, Wenping; Chen, Feng; Huang, Shan; Wang, Chuanxi; Sun, Yongpeng (Frontiers in Energy Research, 2023)
To understand the occurrence state of fracturing fluid in shale gas matrix-fracture system, an experimental method for evaluating fracturing fluid flow characteristics in matrix-fracture system was established. By using Nuclear Magnetic Resonance method, the flow characteristics of fracturing fluid were investigated from three processes of filtration, well shut-in and flowback. The T2 spectrum of fracturing fluid flow process and fracturing fluid saturation in matrix-fracture core model were clarified.The results showdemonstrate that the peak area of T2 spectra increases gradually during the filtration process, and the fracturing fluid quickly fills the fractures and matrix pores. During the well shut-in process, the fracturing fluid gradually flows from the fracture space to the matrix pores, and the signal of the matrix pores increases by 50.5%. During the flowback process, fracturing fluid flows out of the matrix and fracture. And when it reaches a stable state, the peak signal in the fracture decreases by 64.5% and the matrix signal decreasesreduces by 18.8%. The better the porosity and permeability characteristics of the core, the more likely the fracturing fluid is to stay in the formation and cannot be discharged. This paper would contribute to basic parameters for shale gas fracturing design and production strategy optimization.